Effect of H-ZSM-5 zeolite content on the intrinsic kinetics of methanol dehydration to dimethyl ether over H-ZSM-5/Al2O3 molded catalyst. Issue 3 (16th December 2021) - Zhokh, Alexey; Trypolskyi, Andrey; Gritsenko, Valentina; Strizhak, Peter
Abstract : The catalyst composition affects the activation energy and methanol absorption heat, whereas the mechanism of methanol absorption (associative or dissociative) and pre-exponential factor exhibit no sensitivity to catalyst composition. Abstract : A series of H-ZSM-5/Al2 O3 molded catalysts with various zeolite/alumina ratios has been prepared and their catalytic activity in methanol dehydration to dimethyl ether has been studied. Based on the Langmuir–Hinshelwood formalism, several kinetic models involving associative and dissociative mechanisms of methanol adsorption have been investigated. The kinetic parameters of the models have been estimated. The mechanism of methanol adsorption (associative or dissociative) is not sensitive to catalyst composition. The latter also affects the activation energy and methanol adsorption enthalpy, which are associated with the dilution of zeolite acid sites in the alumina matrix. In contrast, preexponential factors exhibit no sensitivity to catalyst composition.